2010
DOI: 10.1055/s-0030-1267229
|View full text |Cite
|
Sign up to set email alerts
|

ACEandACTN3Genotypes in Older Women: Muscular Phenotypes

Abstract: This study examined the association between ACE I/D and ACTN3 R577X polymorphisms and muscle-related phenotypes and their adaptation to resistance training in older women. Volunteers (n=246;age=66.7 ± 5.5 years) underwent quadriceps strength assessment using isokinetics and fat-free mass by dual energy X-ray absorptiometry. 79 volunteers performed 24 weeks of resistance training and 75 were studied as controls. Genotypes were identified by standard procedures. No associations were observed for muscle strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 38 publications
1
42
0
10
Order By: Relevance
“…McCauley et al found no association with indices of muscularity (whole body or thigh non-skeletal lean mass) in older Caucasian men (McCauley et al 2010). In contrast, in the aforementioned study by Lima et al women who were X allele carriers presented higher relative FFM at baseline compared with RR women (Lima et al 2011). Zempo et al (2010) showed that Japanese women with the XX genotype had lower thigh muscle CSA compared with RR and RX genotypes.…”
Section: Cross-sectional Genetic Association Studiesmentioning
confidence: 91%
See 4 more Smart Citations
“…McCauley et al found no association with indices of muscularity (whole body or thigh non-skeletal lean mass) in older Caucasian men (McCauley et al 2010). In contrast, in the aforementioned study by Lima et al women who were X allele carriers presented higher relative FFM at baseline compared with RR women (Lima et al 2011). Zempo et al (2010) showed that Japanese women with the XX genotype had lower thigh muscle CSA compared with RR and RX genotypes.…”
Section: Cross-sectional Genetic Association Studiesmentioning
confidence: 91%
“…strength (using isokinetics) at baseline in Brazilian old women (Lima et al 2011). In contrast, others found an association between the ACTN3 R577X variation and muscle phenotypes in old people, yet with controversial results with regards to which allele (R or X) has a favourable or unfavourable effect.…”
Section: Cross-sectional Genetic Association Studiesmentioning
confidence: 93%
See 3 more Smart Citations